Effects of Ca2+ channel blocker neurotoxins on transmitter release and presynaptic currents at the mouse neuromuscular junction - Katz, E. (1997)
1. The effects of the voltage-dependent calcium channel (VDCC) blockers ω-agatoxin IVA (ω-AgaIVA), ω-conotoxin GVIA (ω-CgTx), ω-conotoxin MVIIC (ω-MVIIC) and ω-conotoxin MVIID (ω-MVIID) were evaluated on transmitter release in the mouse diaphragm preparation. The effects of ω-AgaIVA and ω-MVIIC were also evaluated on the perineurial calcium and calcium-dependent potassium currents, I(ca), and I(K(Ca)), respectively, in the mouse levator auris preparation. 2. The P- and Q-type VDCC blocker ω-AgaIVA (100 nM) and P- Q- and N-type channel blockers ω-MVIIC (1 μM) and ω-MVIID (3 μM) strongly reduced transmitter release (> 80-90% blockade) whereas the selective N-type channel blocker ω-CgTx (5 μM) was ineffective. 3. The process of release was much more sensitive to ω-MVIIC (IC50 = 39 nM) than to ω-MVIID (IC50 = 1.4 μM). After almost completely blocking transmitter release (quantal content ~0.3% of its control value) with 3 μM ω-MVIIC, elevating the external [Ca2+] from 2 to 10 mM induced an increase of ~20 fold on the quantal content of the endplate potential (e.p.p.) (from 0.2 ± 0.04 to 4.8 ± 1.4). 4. Nerve-evoked transmitter release in a low Ca2+-high Mg2+ medium (low release probability, quantal content = 2 ± 0.1) had the same sensitivity to ω-AgaIVA (IC50 = 16.8 nM) as that in normal saline solutions. In addition, K+-evoked transmitter release was also highly sensitive to the action of this toxin (IC50 = 11.5 nM; 100 nM > 95% blockade). The action of ω-AgaIVA on transmitter release could be reversed by toxin washout if the experiments were carried out at 31-33°C. Conversely, the effect of ω-AgaIVA persisted even after two hours of toxin washout at room temperature. 5. Both the calcium and calcium-dependent potassium presynaptic currents, I(ca), and I(K(Ca)), respectively, were highly sensitive to low concentrations (10-30 nM) of ω-AgaIVA. The I(ca), and the I(K(Ca)) were also strongly reduced by 1 μM ω-MVIIC. The most marked difference between the action of these two toxins was the long incubation times required to achieve maximal effects with ω-MVIIC. 6. In summary these results provide more evidence that synaptic transmission at the mammalian neuromuscular junction is mediated by Ca2+ entry through P- and/or Q-type calcium channels.